Open Science Capacity Building in Africa - Havemann, Jo; Bezuidenhout, Louise; Zimmer, Niklas; Owango, Joy (My University, 2022)
List about Open Science Capacity Building stakeholders in Africa that were shared during the First meeting of the Working Group on Open Science Capacity Building hosted by UNESCO.
Keywords: Open Science; Capacity Building; Africa